Camp Hernandez its historical role in Panay Military History (1935-1980s). - Tingzon, Rene J
This study focuses on the historical role of Camp Hernandez, Dingle. Specifically, it aims to:, 1. Present the factors that led to the establishment of Camp Hernandez, Dingle; 2. Describe the role of the camp in terms of local and national security; 3. Show the socio-economic contributions/benefits of the camp to the local people. Since this study mainly uses the historical approach, the major data gathering techniques made use of the study of files, brochures and office records. Data and historical description for the first and second questions were derived from the office records, files and brochures pertaining to the establishment of Camp Hernandez. The third question was derived from field surveys through personal interviews with well-informed citizens of Dingle who can share necessary information about the existence of the camp. This research showed that the main factor that led to the establishment of Camp Hernandez was the preparation of the country for national defense against external threats. The camp was created in 1935 as an attempt to provide a military ground for reserve force and army recruits in preparation for a possible invasion of the country by the Japanese forces. The military role of Camp Hernandez during then American regime and during the Japanese and Republican periods was quite significant. During the American period, Camp Hernandez served primarily as a training ground for army recruits. This was done in order to provide national security as well as to enhance professionalism of the army so as to thwart the external threats against the peace and order of the country. When World War II (Japanese period) broke out, Camp Hernandez became the headquarter of the army reserve forces. However, its function as a training camp and as headquarters were paralyzed when the Japanese warplanes bomb the area. After its fifteen years of abandonment, the camp was revived during the late 1960's (Republcian period). During this period, the camp served as a headquarter for an army unit, training ground for army recruits and bivouac area for CAT and ROTC cadets. From 1970's when the Armed Forces of the Philipines was destabilized by the New People's Army, the camp layed as role in the defense of the country. This can be shown by the deployment of Army units in the camp. (p)Aside from military role played by Camp Hernandez contributes to the socio-economic benefits to the local people. During the American period, the construction of the Camp as well as the roads leading to the area provided employment to the residents because of the labor force of this construction. Also, during the Japanese period, some local industries emerged because of the presence of Camp Hernandez and due to the demand of time.